Prevalence of Maxillary Impacted Canine among Orthodontic Patients of Universal College of Medical Sciences, College of Dental Surgery, Bhairahawa, Nepal - Gupta, Sandeep Kumar; Halwai, Hemant Kumar; Shrestha, Raju (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION In general, canines play an essential role in establishing a functional occlusion as well as serving as the foundation of an esthetic smile. With the exception of the third molars, impaction of the maxillary permanent canines is the most common form of tooth impaction and prevalence of impacted permanent canine has been reported in 1-5% of population. In this study, we aimed to determine the prevalence of maxillary canine impaction among orthodontic patients of Universal College of Dental Surgery, Bhairahawa, Nepal. METHODS A retrospective study was conducted on orthodontic patients at UCMS,CODS during august 2017 to august 2019. The study included clinical examination of 384 patients who visited Department of orthodontics and Dentofacial Orthopedics seeking orthodontic treatment. RESULTS This study reveals, a total of 22 (5.73%) patients having maxillary canine impaction, where 13 (59.09%) were females and 9 (40.90%) were males. Likewise 6 (27.27% ) palatal and 16 (72.72%) buccal maxillary canine impaction was found. CONCLUSION Maxillary canines fulfill important esthetic and functional roles. Unfortunately, prevalence of impacted maxillary canine is approximately 5%, the second highest frequency behind that of third molar impaction. The prevalence of impacted maxillary canine is found to be (5.73%), where 13 (59.09%) were females and 9 (40.90%) were males. Likewise 6 (27.27% ) palatal and 16 (72.72%) buccal maxillary canine impaction was found.